PENGARUH FAKTOR SOSIAL EKONOMI RUMAH TANGGA TERHADAP FERTILITAS (Studi Kasus Desa Moolo Kecamatan Batukara Kabupaten Muna) - Siti Kadarima; Tajuddin Tajuddin; Apoda Apoda (Universitas Halu Oleo, 2021)
This study aims to determine simultaneously and partially the effect of family income, husband's education level, wife's education level, wife's marriage age, wife's length of use of contraceptives, and culture on fertility in Moolo Village, Batukara District, Muna Regency. This study uses a quantitative approach. The population in this study were 154 couples of childbearing age. The number of samples used was 122 people. The results of this study indicate that simultaneously the variables of family income, husband's education level, wife's education level, wife's age of marriage, length of time using contraceptives on wives and culture have a significant effect on fertility. And partially family income (X1) has a significant and positive correlation, the husband's education level (X2) has a significant and negative correlation, the wife's education level (X3) has a significant and negative correlation, the wife's age of marriage (X4) has a significant and negative correlation, The length of time using contraceptives on the wife (X5) has no significant effect and is negatively correlated and culture (Di) has a significant and positive effect on fertility.